2012
DOI: 10.1016/j.neuropharm.2012.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic plus acute prolonged stress on measures of coping style, anxiety, and evoked HPA-axis reactivity

Abstract: Exposure to psychological trauma is the precipitating factor for PTSD. In addition, a history of chronic or traumatic stress exposure is a predisposing risk factor. We have developed a Chronic plus Acute Prolonged Stress (CAPS) treatment for rats that models some of the characteristics of stressful events that can lead to PTSD in humans. We have previously shown that CAPS enhances acute fear responses and impairs extinction of conditioned fear. Further, CAPS reduced the expression of glucocorticoid receptors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 75 publications
1
45
0
Order By: Relevance
“…Many studies have shown that, consistent with PTSD models, SPS increased serum CORT concentrations, and decreased the sucrose preference of rats (Kozlovsky et al ., 2009; Roth et al ., 2012; Meyer et al ., 2013). Accordingly, the forced maintenance of high CORT levels and the decrease in sucrose preference associated with animal models can affect anxiety- and depression-like symptoms under experimental conditions, and this may be related to the progression or exacerbation of PTSD in humans (Serova et al ., 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that, consistent with PTSD models, SPS increased serum CORT concentrations, and decreased the sucrose preference of rats (Kozlovsky et al ., 2009; Roth et al ., 2012; Meyer et al ., 2013). Accordingly, the forced maintenance of high CORT levels and the decrease in sucrose preference associated with animal models can affect anxiety- and depression-like symptoms under experimental conditions, and this may be related to the progression or exacerbation of PTSD in humans (Serova et al ., 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…The NSFT was performed on Day 10 (see Figures 1A and 1B) and carried out as originally described by Bodnoff et al (1988) and by us previously (Furmaga et al, 2011, Roth et al, 2012). Rats were food deprived for 24 or 48 h prior to testing.…”
Section: Methodsmentioning
confidence: 99%
“…Although there exists large body of evidence demonstrating the negative impact of stress on emotional symptoms including depression, anxiety (Millan et al, 2012) and cognitive impairment (Alzoubi et al, 2013a; Devilbiss et al, 2012; Jonsdottir et al, 2013; Ohman et al, 2007; Ronnlund et al, 2013; Schwabe et al, 2012), however, studies investigating role of stress in comorbid prevalence of anxiety, depression and cognitive impairment in humans (Andreotti et al, 2013; Millan et al, 2012), or co-occurrence of anxiety and depression-like behaviors as well as learning-memory impairment, in animals are limited (Gomez et al, 2013; Haridas et al, 2013). Although impressive mechanistic insights have been offered by several groups, with regards to co-occurrence of anxiety-and depression-like behaviors in animal models (Mineur et al, 2013; Roth et al, 2012; Venzala et al, 2012), studies addressing the underlying biology of stress-induced co-occurrence of depression, anxiety and cognitive impairment are scarce.…”
Section: Introductionmentioning
confidence: 99%